(untitled) (Jahangirnagar University Journal of Biological Sciences, 2022)
Small indigenous species (SIS) of fishes are available source of animal protein, vitamin and minerals, not commonly available in other foods in Bangladesh. These fishes are eaten both in fresh and dried condition. Puntious sophore was collected from different regions of Baikka Beel at Sreemangal Upazila, Moulvibazar district, Bangladesh to investigate mycoflora association with dried condition. Fungus was isolated from dried fish using tissue planting methods for classical and molecular characterization. Aspergillus elegans was identified through classical taxonomy and molecular approach based on ITS region of ribosomal DNA (rDNA) of fungi. For analyzing ITS4 and ITS5 were used. Mycelium of the identified fungus septated, hyaline, abundant and branched. Long, straight or flexous conidiophore were present. The molecular phylogeny in morphologically identified dry fish fungi of P. sophore such as A. elegans was studied based on their internal transcribed spacer (ITS). The sequences of ITS 600 bp region of A. elegans had 5.8S of rDNA sequences were identical. The highest mycelial growth was recorded in potato dextrose agar (PDA) medium for the growth and development of A. elegans. Temperature 30°C was optimum, this fungus grew well in pH 7. So, tested fungi grew well in neutral condition. Jahangirnagar University J. Biol. Sci. 10(1 & 2): 39-47, 2021 (June & December)